Agrobacterium rhizogenes-mediated hairy root of apple of sodom (Solanum mammosum L.) for optimized production of solasodine - Ooi, Chai Theam (2015)
The increasing demand of diosgenin for high-revenue synthesis of useful steroid hormones such as progesterone and cortisone by the pharmaceutical industries has driven researchers to look for other alternatives to replace this compound in order to prevent the increase of price of the end products. The aglycone of the steroidal alkaloid, solasodine, which was reported to be present in Solanum mammosum,can replace diosgenin and be converted to 16-dehydropregnenolone, which is a key intermediate in the synthesis of steroid hormones. In order to produce more solasodine from S. mammosum in a shorter period of time, hairy root culture mediated by Agrobacterium rhizogenes was established in this study. Besides that, the production of solasodine from transformed hairy culture of S. mammosum has not been reported previously. In order to increase the number of transformants to enable a wider selection of better transformants which were highly productive both in terms of biomass growth as well as the production of secondary metabolites of interest, optimization of the protocol for hairy root induction using five different strains of A. rhizogenes, that are, strain ATCC31798, ATCC43057,AR12, A4 and A13, on the leaf explants of S. mammosum has been carried out in the present study. Furthermore, in order to enhance the production of solasodine,the culture conditions of the transformed hairy root cultures were optimized through medium manipulation, elicitation and precursor feeding. The results showed that by adding 300 μM methyl jasmonate, 100 μM cholesterol, and 1000 μM L-arginine into the culture medium (liquid modified MS medium with ammonium to nitrate ratio of 10.3 mM : 39.4 mM and 4 % (w/v) sucrose) at day 20 of the culture could improve the solasodine content in both the hairy root line- ATCC31798 and line-A4 induced by A. rhizogenes strain ATCC31798 and A4 respectively. The solasodine productivity for hairy root line-ATCC31798 was 4.44 ± 0.42 mg/g dry weight roots and line-A4 was 4.55 ± 0.42 mg/g dry weight roots with a total biomass of 188.7 ± 21.7 mg and 176.7 ± 23.4 mg respectively on dry weight basis after 32 days of culture under 16-hour light / 8-hour dark regime,when using 50 mg fresh weight roots as initial inoculum size. The solasodine yield for both hairy root lines was at least nine times higher than those before any optimization. The improved solasodine production while maintaining a relatively high biomass yield could reduce the cost for steroid synthesis in the pharmaceutical industry in the long run.